Donor‐dominant one‐way matching of human leukocyte antigen‐A/B/DR alleles predicts graft‐versus‐host disease following living donor liver transplantation. Issue 1 (20th October 2020) - Hirata, Masaaki; Yagi, Shintaro; Shindo, Takero; Yoshizawa, Atsushi; Kiguchi, Gozo; Kaneshiro, Masakatsu; Yurugi, Kimiko; Miyachi, Yosuke; Iwamura, Sena; Yao, Siyuan; Uemoto, Shinji
Abstract : Aim: Graft‐versus‐host disease (GVHD) following liver transplantation is rare but fatal. Therefore, it is important to identify possible risk factors before transplantation. Although it has been suggested that donor‐dominant one‐way human leukocyte antigen (HLA) matching of three loci (HLA‐A/B/DR) is associated with the occurrence of GVHD, the precise significance of HLA matching including HLA‐C/DQ/DP remains unclear. Methods: We retrospectively analyzed the impact of donor‐dominant one‐way HLA matching at six HLA loci at the allele level on GVHD using clinical registry data from 1759 cases who underwent living donor liver transplantation between June 1990 and June 2019. We extracted cases with donor‐dominant one‐way HLA matching at the antigen level and reconfirmed them at the allele level using preserved DNA samples. Results: Three of four cases (75%) who developed GVHD showed donor‐dominant one‐way HLA matching at three HLA‐A/B/DR loci. These cases also showed donor‐dominant one‐way HLA matching at HLA‐C/DQ/DP. Three of six cases (50%) with donor‐dominant one‐way HLA matching at three loci of HLA‐A/B/DR developed GVHD. Notably, none of the cases with donor‐dominant one‐way HLA matching at one or two HLA‐A/B/DR loci developed GVHD, irrespective of matching status at HLA‐C/DQ/DP. The HLA matching status at the antigen level was revised in 22 of 56 cases, following reconfirmation at the allele level. Conclusions: Pairing of donors and recipients with donor‐dominant one‐way HLA matching at three HLA‐A/B/DR loci should be avoided to prevent GVHD. No impact of HLA‐C/DQ/DP on GVHD was identified. For liver transplantation, HLA genotypes should be determined at the allele level.